Academic Integrity and Mental Well-being: Exploring an Unexplored Relationship - Pethrick, Helen; Eaton, Sarah Elaine; Turner, Kristal Louise (Canadian Perspectives on Academic Integrity, 2021)
The rapid and accelerated shift to online learning during the COVID-19 pandemic has heightened parallel conversations about student well-being and academic integrity in higher education. On one hand, post-secondary students have been under increased pressure to succeed in stressful learning and societal environments. On the other hand, reports of student academic misconduct have increased throughout the COVID-19 pandemic. There is an urgent need to consider the intersecting relationship between mental well-being and academic integrity to foster supportive, learner-focused, and caring higher education environments. In this session, we will open a conversation about this widely unexplored relationship. We will present the findings of a rapid review wherein we investigated how the academic integrity literature had taken up mental well-being. We will address ways that student well-being should be considering in academic integrity research and practice, such as the need to care for student well-being during academic misconduct incidents. Participants will leave this session with lessons that will be applicable during the ongoing COVID-19 pandemic and beyond.